Primary Cutaneous Melanoma Arising in a Long-Standing Irradiated Keloid. (7th February 2012) - Fish, Lindsay M.; Duncan, Lisa; Gray, Keith D.; Bell, John L.; Lewis, James M.
Abstract : Ionizing radiation has been used therapeutically for a variety of clinical conditions, including treatment of hypertrophic keloids. Keloids may rarely be associated with malignancy, but the use of low-dose ionizing radiation is associated with an increased risk of cutaneous malignancies. We describe a case in which a primary desmoplastic melanoma arose in a long-standing, previously irradiated keloid.